Activity patterns of terrestrial frugivorous mammals in a Mexican Neotropical forest - Mendoza, Eduardo; Camargo-Sanabria, Angela A; Basurto-Godoy, Juan; Godínez-Gómez, Oscar; Mendoza Ramírez, Manuel (THERYA, 2019)
Fruits reaching the floor of tropical forests constitute an attractive resource for a variety of mammals. Study of the characteristics of the frugivory interaction can help to advance in the understanding of the mechanisms favoring animal’s coexistence. However, there are few studies focused on analyzing patterns of activity of mammals feeding on fruits in the forest floor. Camera traps were used to record consumption of Licania platypus and Pouteria sapota fruits by Cuniculus paca, Dasyprocta punctata, Nasua narica, Dycotiles crassus and Tapirella bairdii. Patterns of mammal activity were characterized based on the day, time and tree in which they were recorded. Overlap in daily (delta coefficient) and spatial occurrence (same tree and day, Jaccard, Ochiai indices and V ratio) was assessed. High segregation in the activity of frugivores occurred during the day (mean 0.291 and 0.191 for L. platypus and P. sapota, respectively) and among trees/days (max. Jaccard = 0.14 and 0.19 for L. platypus and P. sapota, respectively). Our results suggest that activity overlap among mammalian frugivores feeding in the forest floor is lower than expected. This likely relates to the fact we conducted our analysis at a finer detail than previous studies (for example those focusing exclusively on dietary overlap). Thus, our study increases our understanding of the possible factor that can favor coexistence of tropical frugivorous mammals.